Special features of the use of telemedicine technologies in dermatology - Avrunin, O. G.; Аврунін, О. Г.; Isaieva, O.; Trubitsin, A.; Strelchenko, D. (Odesa I. I. Mechnikov National University, 2020)
The article focuses on the application of telemedicine technologies in dermatology. The usage of telemedicine approach makes it possible to study certain skin pathologies remotely and monitor the progress of the treatment in the dynamics. The use of equipment and telemedicine services for the study of skin diseases is explained. The dermatoscopic telemedicine system is described. The possibilities of using mobile telemedicine in dermatology are analyzed.
Keywords: telemedicine; image processing; mobile dermatology; dermatoscopy; dermatology